Design and implementation of a rotary parking system for a truly smart city in line with smart cities technologies and trends - Mahmood M.A.; Hajjaj S.S.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control systems; Smartphones; Automated parking; Autonomous Parking; Design and implementations; Human population; Identifying methods; Mechanical design; Parking systems; Simulated system; Smart city